Expression of TCR‐Vβ peptides by murine bone marrow cells does not identify T‐cell progenitors. Issue 8 (6th March 2015) - Abbey, Janice L.; Karsunky, Holger; Serwold, Thomas; Papathanasiou, Peter; Weissman, Irving L.; O'Neill, Helen C.
Abstract Germline transcription has been described for both immunoglobulin and T‐cell receptor (TCR) genes, raising questions of their functional significance during haematopoiesis. Previously, an immature murine T‐cell line was shown to bind antibody to TCR‐Vβ8.2 in absence of anti‐Cβ antibody binding, and an equivalent cell subset was also identified in the mesenteric lymph node. Here, we investigate whether germline transcription and cell surface Vβ8.2 expression could therefore represent a potential marker of T‐cell progenitors. Cells with the TCR phenotype of Vβ8.2+Cβ− are found in several lymphoid sites, and among the lineage‐negative (Lin−) fraction of hematopoietic progenitors in bone marrow (BM). Cell surface marker analysis of these cells identified subsets reflecting common lymphoid progenitors, common myeloid progenitors and multipotential progenitors. To assess whether the Lin−Vβ8.2+Cβ− BM subset contains hematopoietic progenitors, cells were sorted and adoptively transferred into sub‐lethally irradiated recipients. No T‐cell or myeloid progeny were detected following introduction of cells via the intrathymic or intravenous routes. However, B‐cell development was detected in spleen. This pattern of restricted in vivo reconstitution disputes Lin−Vβ8.2+Cβ− BM cells as committed T‐cell progenitors, but raises the possibility of progenitors with potential for B‐cell development.